Peran Rekrutmen dan Penempatan Kerja pada PT. Indomarco Adi Prima Surabaya - Rohmah, Novika Nur; Frianto, Agus (Jurnal Ilmu Manajemen, 2021)
This study examines the role of recruitment and job placement at PT. Indomarco Adi Prima Surabaya influence work productivity. This research with a quantitative approach has 60 populations. The tests performed were data analysis of validity, reliability, and classic assumption tests, including normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. Furthermore, hypothesis testing includes test (R2), T statistical test, F statistical test, and multiple linear regression test. Data collection use observations, interviews and (primary) questionnaires. Data analysis use multiple linear regression with SPSS (v.18). The results showed that partially and simultaneously, the variables of recruitment and job placement had a significant positive effect on employee work productivity. Partially the better the recruitment system, the better work productivity will be. Likewise, a good job placement will increase employee work productivity. Furthermore, simultaneously the variable recruitment and good work placement will increase employee productivity.